Successful Implementation of SDG'S Concept in Citra Raya Tangerang Housing - Muhammad Afiq Riwendi; Nurahma Tresani; Lana Winayati (Publikasi Indonesia, 2024)
Citra Raya Tangerang is an area developed by the Ciputra Group since 1994; since 2011, Citra Raya Tangerang has implemented the EcoCulture concept, which is expected to turn residents into a green community that cares about a clean environment. The EcoCulture concept has similarities with sustainable development or SDGs, which aims to eradicate poverty, improve prosperity and care for the planet Earth. 17 (seventeen) achievements are used as indicators of achieving sustainable development. To achieve these 17 (seventeen) achievements cannot be done alone; collaboration between various parties is needed to achieve these goals. Citra Raya Tangerang, by implementing the EcoCulture concept since 2011, has succeeded in achieving seven goals out of 17 indicators of sustainable development. The achievements that Citra Raya Tangerang has made are number 3. Good Health and Well-Being, 6. Clean Water and Sanitation, 7. Affordable and Clean Energy, 8. Decent Work and Economic Growth, 11. Sustainable Cities and Communities, 12. Responsible Consumption and Protection, 13. Climate Action. The achievement of these seven indicators was not carried out by Citra Raya Tangerang alone but involved several other stakeholders. This stakeholder consistency applies the things that are part of this indicator so that the prepared plan can run well. Residents who consistently sort waste, local governments who provide support and other third parties who collaborate to achieve this goal. Citra Raya Tangerang management continues to strive to provide the best service to its residents. The effect of this collaboration means that sustainable development goals can be achieved gradually.